TINJAUAN PELAKSANAAN PELAYANAN TERHADAP PENGAJUAN KLAIM NASABAH ASURANSI KENDARAAN BERMOTOR ( Studi Kasus PT Asuransi Sinar Mas Jakarta) - Vera Agustina Yanti (Cakrawala - Jurnal Humaniora, 2012)
The role of service to smooth the process of filing a claim often experience barriers of problem s canoccur for many reasons that come from internal and external parties . Such as the incompleteness ofthe data as a condition of insurance customers filling a claim , due to the transfer of premiumcontinued missinformation by agents of fault repairs that are inconsistent with claims field bycustomers, of delay in the handling of insurance customers making it difficult for service personel inthe service of the service process and hamper the process of filling a claims for writing intended to seeto what extent the role of service in helping to smooth the process of filling insurance claims on the PTAsuransi sinar mas the process claim is insurance customers to bring the data completenessrequirements ,contact the service, and conducted a survey and analysis service of the insured vehicle.Various efforts and strategies carried out by the company to meet customers needs it is proved by theincrease of policy in number 21.226 in year 2010 and the year 2011 =22.675 . it shows confidence andcustomers satisfaction increase insurance .Key words: filing a claim, implementation of service, insurance